Augmented Reality Technology For Arabic Vocabulary Learning As A Model Of Quran Reflection For Hearing-impairment Adults - Nabilah Fasihah Ahmad Yusoff; Ummu-Hani Abas; Mohammad Najib Jaffar; Ahmad Asyraf Mat Ali; Mohammad Lukman Al-Hakim Md. Noor; Mohd Fadzil Abdul Hanid; Norakyairee Mohd. Raus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Indexed by WOS